Postoperative exercise rehabilitation after elective colorectal cancer surgery - Paul, Melanie Alya (2025)
Introduction Colorectal cancer (CRC) is common, accounting for approximately 11% of all new cancer cases, and is primarily a cancer associated with increasing age (Cancer Research UK, 2021). Surgery is usually the most appropriate option (if feasible and depending on staging) to try to achieve cancer free status. However, it carries significant morbidity, especially given the generally older patient population in which colorectal cancer presents (Argillander et al., 2021; Kolarsick et al., 2020). Appropriately stratifying preoperative risk to improve immediate outcomes is an appropriate strategy, but after a significant physiological insult through surgery, patients are not given clear guidance on how to regain their preoperative physical state (Karlsson et al., 2020). A structured exercise programme, such as proposed within this thesis, aims to assess the use of both aerobic and resistance exercises to safely improve postoperative patients’ physical and mental fitness and wellbeing, looking at objective measures through cardiorespiratory exercise testing (CPET) but also milestones important to the patient such as the ability to carry out their activities of daily living in order to improve not only their speed of recovery but maintain their mental well-being during a difficult period.